A comparison of virtual bronchoscopy versus flexible bronchoscopy in the diagnosis of tracheobronchomalacia in children. Issue 4 (18th September 2016) - Su, Siew Choo; Masters, Ian Brent; Buntain, Helen; Frawley, Kieran; Sarikwal, Anubhav; Watson, Debbie; Ware, Frances; Wuth, Jan; Chang, Anne Bernadette
Summary: Introduction: Flexible bronchoscopy (FB) is the current gold standard for diagnosing tracheobronchomalacia. However, it is not always feasible and virtual bronchoscopy (VB), acquired from chest multi‐detector CT (MDCT) scan is an alternative diagnostic tool. We determined the sensitivity, specificity, and positive and negative predictive values of VB compared to FB in diagnosing tracheobronchomalacia. Methods: Children aged <18‐years scheduled for FB and MDCT were recruited. FB and MDCT were undertaken within 30‐min to 7‐days of each other. Tracheobronchomalacia (mild, moderate, severe, very severe) diagnosed on FB were independently scored by two pediatric pulmonologists; VB was independently scored by two pairs (each pair = pediatric pulmonologist and radiologist), in a blinded manner. Results: In 53 children (median age = 2.5 years, range 0.8–14.3) evaluated for airway abnormalities, tracheomalacia was detected in 37 (70%) children at FB. Of these, VB detected tracheomalacia in 20 children, with a sensitivity of 54.1% (95%CI 37.1–70.2), specificity = 87.5% (95%CI 60.4–97.8), and positive predictive value = 90.9% (95%CI 69.4–98.4). The agreement between pediatric pulmonologists for diagnosing tracheomalacia by FB was excellent, weighted κ = 0.8 (95%CI 0.64–0.97); but only fair between the pairs of pediatric pulmonologists/radiologists for VB, weighted κ = 0.47 (95%CI 0.23–0.71). There were 42 cases of bronchomalacia detected on FB. VB had a sensitivity = 45.2% (95%CI 30.2–61.2), specificity = 95.5% (95%CI 94.2–96.5), and positive predictive value = 23.2 (95%CI 14.9–34.0) compared to FB in detecting bronchomalacia. Conclusion: VB cannot replace FB as the gold standard for detecting tracheobronchomalacia in children. However, VB could be considered as an alternative diagnostic modality in children with symptoms suggestive of tracheobronchomalacia where FB is unavailable. Pediatr Pulmonol. 2017;52:480–486. © 2016 Wiley Periodicals, Inc.